Analisis Metode Pengendalian Pemesanan Bahan Baku Penolong Roda Kereta Api (Bogie) PT. Barata Indonesia Di Gresik - Elan, Umi; Fahmi, Mohammad Alvin (GEMA EKONOMI, 2019)
This study tries to study the method of converting the auxiliary raw materials for the best train wheels (bogie) at PT. Barata Indonesia. This research is important in reducing the total cost of completion issued by PT. Barata Indonesia. This study uses descriptive quantitative method of submission of raw materials in the form of Economic Order Quantity (EOQ), and Just In Time (JIT). Pepset P-02 will be better by using the Economic Order Quantity (EOQ) method, while the control of Kalminex Type FM 100-A100 / 130 raw materials will be better by using the Just In Time (JIT) method Keyword: EOQ, JIT, Total Inventory CostDOI : 10.5281/zenodo.3474547